Dítě, nebo tradice? Plánování vzdělávacího obsahu v předškolním vzdělávání - Eva Koželuhová; Barbora Loudová Stralczynská; Zora Syslová (Karolinum Press, 2023)
The paper deals with the issue of curriculum development in pre-primary education. The aim of the research was to find out what experiences and opinion student-teachers have to the development of school and class curricula. The data were obtained through a questionnaire conducted between 2020−21 among students of BA and MA part-time programmes of faculties preparing preschool teachers in the Czech Republic (N = 1001, response rate 35%). For this paper, data from respondents working as teachers in preschools (N = 224) were used. The results showed that the approaches of preschools are heavily burdened by the pedagogical tradition of the sociocentric paradigm. A chronological approach to the arrangement of educational content in school curricula prevails (63%). Almost a third of preschools create classroom curricula for the whole year ahead. Only 44% of respondents suggest educational topics during the school year. In contrast, more flexible approaches, justified by respect for the child, dominated respondents' preferences. In spite of this, the lack of understanding of the current notion of designing educational content at school and classroom level were still very much present in the sub-statements.